The Distance Matrices of Some Graphs Related to Wheel Graphs - Xiaoling Zhang; Chengyuan Song (Journal of Applied Mathematics)
Let D denote the distance matrix of a connected graph G. The inertia of D is the triple of integers (n+(D), n0(D), n-(D)), where n+(D), n0(D), and n-(D) denote the number of positive, 0, and negative eigenvalues of D, respectively. In this paper, we mainly study the inertia of distance matrices of some graphs related to wheel graphs and give a construction for graphs whose distance matrices have exactly one positive eigenvalue.